Іnvestigation of plasma of arc discharge between melting Cu- and Ni-electrodes - Kleshich, M.M.; Veklich, A.N.; Fesenko, S.O.; Boretskij, V.F.; Kryachko, L.A. (Вопросы атомной науки и техники, 2018)
Plasma of electric arc between asymmetric one-component Cu and Ni electrodes was investigated by optical emission spectroscopy. Radial distributions of temperature and electron density were determined in the average cross section of arc column. Plasma composition was calculated on the base of experimentally obtained temperatures and electron densities as initial data in the assumption of local thermodynamic equilibrium. It was found that a cathode surface plays predominated role as a erosion source of metal vapors in arc discharge plasma. The proposed technique can be used for estimation of the erosion properties of different contact materials.